2001
DOI: 10.1039/b008903f
|View full text |Cite
|
Sign up to set email alerts
|

Superbasic bridgehead diphosphines: the effects of strain and intrabridgehead P  · · ·  P bonding on phosphine basicity

Abstract: The basicity order in acetonitrile for a series of phosphines is: 1,5-diphosphabicyclo [3.3.3]undecane 1 (pK a for the protonated ion ~17.9) < 1, 6-diphosphabicyclo[4.3.3]dodecane 2 (pK a ~22.5) < 1,6-diphosphabicyclo[4.4.3]tridecane 3 (pK a 27.8). The latter is therefore comparable to Schwesinger's P 1 -t-Bu base but still significantly weaker than Verkade's proazaphosphatrane bases. The pK a for the protonated ion of 1,6-diphosphabicyclo[4.4.4]tetradecane 4 could not be determined due to rearrangement probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…[13][14][15][16][17][18][19][20] Phosphatrane molecules are a tricyclic cage-like heterocycles which present the possibility to have a transannular dative bond with a nitrogen or another heteroatom. The pioneer synthetic work in the groups of Alder and Verkade [21][22][23][24][25][26][27][28][29] showed that depending of the size, substituents and environment they can adopt out:out and/or in:out conformations. In previous works, we have demonstrated that the change of the conformation can have profound implications in the nucleophilic character of the terminal phosphorous atom, and thus, the equilibrium between out:out and in:out conformation can be tuned through the interaction with Lewis acids.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Phosphatrane molecules are a tricyclic cage-like heterocycles which present the possibility to have a transannular dative bond with a nitrogen or another heteroatom. The pioneer synthetic work in the groups of Alder and Verkade [21][22][23][24][25][26][27][28][29] showed that depending of the size, substituents and environment they can adopt out:out and/or in:out conformations. In previous works, we have demonstrated that the change of the conformation can have profound implications in the nucleophilic character of the terminal phosphorous atom, and thus, the equilibrium between out:out and in:out conformation can be tuned through the interaction with Lewis acids.…”
Section: Introductionmentioning
confidence: 99%
“…The target bis-(phosphane) building blocks for such an approach are shown in Scheme 1, and feature a pair of metal-bearing tripodal tris(amido)phosphane ligands, as well as a bridge between the metal centers labeled M. The addition of suitable late-transition-metal fragments capable of bonding to two phosphane moieties, labeled MЈL n in Scheme 1, should provide a facile route to transition-metal-containing oligomers and polymers. Although there are a plethora of examples of bis(phosphanes) used as bridging ligands, [22][23][24] as well as flexible ligands incorporating hard and soft donors that have been utilized as building blocks for bimetallic and polynuclear early-late transition-metal clusters, [25,26] the complexes we propose here could provide rare examples of linear bis(phosphane) building blocks, [27][28][29][30][31][32] where throughspace interactions provide the potential for extended interactions. In this paper, we test the synthetic feasibility of preparing such building blocks using the diamagnetic early transition metals zirconium and titanium, with the goal of introducing redox active and paramagnetic metal-bridge fragments in future endeavours.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions with excesses of appropriate nucleophiles then afforded the demetalated diphosphines in good yields . Interestingly, the “largest” such diphosphine previously synthesized consisted of one (CH 2 ) 3 and two (CH 2 ) 4 bridges …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Interestingly,t he "largest" such diphosphinep reviously synthesized consisted of one (CH 2 ) 3 and two (CH 2 ) 4 bridges. [6] Macrobicyclic dibridgehead diphosphines, such as 1c,e,a re capable of homeomorphism, [7] ad ynamic process that was defined 50 years ago, butr emains unfamiliar to many chemists. As exemplified with 1c and adducts thereof in Scheme 2, one bridge is threaded through the other two, which effectively turns the molecules inside out.…”
Section: Introductionmentioning
confidence: 99%